Nanomechanical properties of potato flakes using atomic force microscopy. (October 2021) - Al-Rekabi, Zeinab; Davies, Suzanne L.; Clifford, Charles A.
Abstract: Characterizing the nanomechanical properties of plants at the sub-cellular level is important in understanding the dynamic processes underpinning both potato plant growth and downstream effects of industrial food processing. Here, we measured nanomechanical properties and mapped the elastic properties of two types of industrial potato flakes that provide both optimal and sub-optimal results during food manufacturing by employing both amplitude-modulation and force-modulation atomic force microscopy (AFM) in air. The amplitude-modulation AFM revealed that sub-optimal potato flakes were more compliant when compared to the optimal samples. Furthermore, the elastic modulus maps demonstrated optimal potato samples to be significantly stiffer than the sub-optimal samples. Therefore, our results provide evidence that probing the elastic properties of potato flakes can be a first step in providing food industries with a quantitative differential assessment between optimal and sub-optimal samples. Highlights: Potato flakes are a key base ingredient in many processed food and snack products. Flakes are grouped as either optimal or sub-optimal depending on their stability to produce a finished product snack. Elastic modulus from two different techniques quantitatively map changes in the nanomechanical properties of potato flakes. Sub-optimal potato flakes appear more compliant than the optimal samples. Quantitative AFM measurements provide a differential assessment between optimal and sub-optimal batches of potato flakes.